Diversity of the Mesostigmata (Acari) in tree-hollows of selected deciduous tree species - Kaczmarek, Sławomir; Marquardt, Tomasz; Faleńczyk-Koziróg, Katarzyna (Biological Letters, 2011)
Rich gamasid communities were found in tree-hollows of horse chestnut (Aesculus hippocastanum), small-leaved lime (Tilia cordata), and white willow (Salix alba) in urban and rural areas in northern Poland (Bydgoszcz and its environs). We recorded there 93 gamasid species of 21 families in a total of 18 tree-hollows. Differences in the dominance structure of gamasid communities at the levels of family and species indicated dissimilarities in the mite communities, depending on tree species and intensity of human impact. The chestnut tree-hollows in both areas were dominated by mites of the family Urodinychidae (with the dominant Uroobovella pyriformis in both cases). The lime tree-hollows were colonized mostly by the Trematuridae (Trichuropoda ovalis) and the Digamasellidae (Dendrolaelaps tenuipilus) in the rural area, whereas by the Ascidae (Iphidozercon gibbus) in the city. The gamasid communities of willow hollows were dominated by the Trematuridae (Trichouropoda ovalis) in the urban area, and by the Digamasellidae (Dendrolaelaps longifallax, D. zwoelferi) in the rural area. Some rare species (e.g. Microgynium rectangulatum or Microsejus truncicola) were also recorded, mostly in the rural area.